Pelatihan Relaksasi Otot Progresif Dengan Musik Klasik Terhadap Pengetahuan Stress dan Tekanan Darah Pasien Hipertensi - Boru Gultom, Agustina; Batubara, Arbani; Hayati Sihombing, Nurmala (Yayasan Inspirasi El Burhani, 2025)
Background: Hypertensive patients experience problems when their blood pressure increases and will experience premature death if not treated. The magnitude of the hypertension problem lies in proper treatment, the patient's ability to control the disease, compliance with treatment and stress management. Mulyorejo Health Center has made efforts to control blood pressure in hypertensive patients, but these efforts still need to be improved. Objective: The purpose of community service activities is so that people with hypertension will experience increased knowledge, decreased stress and blood pressure through progressive muscle relaxation training with classical music. Method: Community service activities use a quasi-experimental design without a control group. Measurement of knowledge using a questionnaire, stress using the SUDS (Subjective Units of Distress Scale) questionnaire and blood pressure using an Omron digital tensiometer. Then continued with intervention in the form of progressive muscle relaxation accompanied by classical music in hypertensive patients with lecture methods, questions and answers, demonstrations and redemonstrations for progressive muscle relaxation activities accompanied by classical music. Then, re-measure knowledge, stress and blood pressure using the same questionnaire and tools. The target of this activity was 20 hypertensive patient. Results: The results of this community service activity showed a p-value of 0.0030 for knowledge, 0.0001 for stress, 0.0001 for systolic blood pressure, and 0.0010 for diastolic blood pressure. Conclusion: Progressive muscle relaxation training accompanied by classical music significantly increased knowledge and reduced stress and blood pressure in hypertensive patients.